Palosuran Treatment Effective as Bosentan in the Treatment Model of Pulmonary Arterial Hypertension - Pehlivan, Yavuz; Dokuyucu, Recep; Demir, Tuncer; Kaplan, Davut Sinan; Koc, Ibrahim; Orkmez, Mustafa; Onat, Ahmet Mesut (Springer/Plenum Publishers, 2014)
Pulmonary arterial hypertension (PAH) is a progressive and fatal disorder that any valuable advance in the management of diseases has crucial importance. The present study aimed to compare the Endothelin1 (ET1) inhibitor bosentan which is regarded as standard therapy with different dose regimens of palosuran which is urotensin-II (UII) inhibitor and explore the discrepancy for mean pulmonary arterial pressure (mPAP), UII, ET1 levels, and pulmonary vascular pathology. Seventy rats were randomly divided into seven groups of ten animals each: group 1 (control group) received the vehicle subcutaneously, instead of monocrotaline (MCT) and vehicle; group 2 (MCT group) received subcutaneous MCT and vehicle; and group 3 (MCT + palosuran 30 mg) received subcutaneous MCT and palosuran. Other groups consist of group 4 (MCT + palosuran 100 mg), group 5 (MCT + bosentan 30 mg), group 6 (MCT + bosentan 100 mg), and group 7 (combination therapy). Serum ET1, UII, mPAP levels, and pulmonary arteriolar pathology of different diameter vessels of all groups have been measured and recorded. The ET1 and UII levels of untreated rats (group 2) were significantly higher than the other groups (p < 0.05). Moreover, mPAP levels of group 2 were significantly higher than the other groups (p = 0.001). Finally, 50-125-mu m diameter of arteriole wall thickness was found to be significantly thicker in monocrotaline group compared to groups 4 and 6 (p < 0.001). Statistical differences of wall thickness/diameter ratios of arteries and arterioles larger than 125 was found to be significant between group 5, group 6, and the control group (p < 0.001). UII inhibitor is at least as effective as standard therapy bosentan. Findings of this study consolidate that palosuran could be a new future promising therapeutic option in PAH.
Keywords: pulmonary arterial hypertension; urotensin-II antagonist; palosuran